2021
DOI: 10.2196/26029
|View full text |Cite
|
Sign up to set email alerts
|

A Cyberbullying Media-Based Prevention Intervention for Adolescents on Instagram: Pilot Randomized Controlled Trial

Abstract: Background Between 15% and 70% of adolescents report experiencing cybervictimization. Cybervictimization is associated with multiple negative consequences, including depressed mood. Few validated, easily disseminated interventions exist to prevent cybervictimization and its consequences. With over 97% of adolescents using social media (such as YouTube, Facebook, Instagram, or Snapchat), recruiting and delivering a prevention intervention through social media and apps may improve accessibility of pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 65 publications
0
37
0
1
Order By: Relevance
“…Cyberbullying had a negative impact on students on mental health aspects including depression, social anxiety, suicide, low self-esteem and behavioral problems that can strain relationships between family members. 1 , 7 , 18 In addition, cyberbullying could reduce student’s achievement in school. Other studies have shown that bullying causes a deficit in emotional abilities, which has an impact on psychological dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Cyberbullying had a negative impact on students on mental health aspects including depression, social anxiety, suicide, low self-esteem and behavioral problems that can strain relationships between family members. 1 , 7 , 18 In addition, cyberbullying could reduce student’s achievement in school. Other studies have shown that bullying causes a deficit in emotional abilities, which has an impact on psychological dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…A potential reason may have been the low levels of distress at baseline, which made improvements harder to detect. 14 Kutok et al ( 2021 ) (USA, Pilot RCT) Adolescents with past experience of cybervictimization (15.3) 1. IMPACT 2.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Kutok et al [ 39 ] studied IMPACT (Intervention Media to Prevent Adolescent Cyber-Conflict Through Technology), which consists of a brief and remote app-based intervention developed in the USA to reduce the negative effects of cyberbullying and improve bystanders’ intervention. In particular, between 30 January 2020 and 3 May 2020, a national sample of 80 adolescents with a history of past-year cybervictimization was recruited by using some targeted Instagram advertisements for a randomized control trial of IMPACT.…”
Section: Resultsmentioning
confidence: 99%
“…With the same objectives in mind, other interventions point to stimulating youngsters’ emotional education in a less conventional way by interacting in a theatre performance on the theme (as in ACT Out! [ 27 ]) or by developing apps, videogames, or automated SMS text-messaging to deliver the intervention remotely (as in IMPACT [ 39 ], in Cooperative Cybereduca 2.0 [ 43 ], and in the study by Ranney [ 41 ], respectively).…”
Section: Discussionmentioning
confidence: 99%